ANALYSIS OF MEDICAL SERVICE CONTROL PROCESS IN THE SCOPE OF COMPULSORY HEALTH INSURANCE PROGRAM - M. A. Taranik; G. D. Kopanitsa (Бюллетень сибирской медицины)
The relevance of the presented paper deals with the necessity of determining problems and effective solutions for medical organizations on the stage of medical documentation reports control purposely for forecasting the average of financial resources that can be obtained in the scope of compulsory health insurance program.The aim of the study – for the purpose of further issues definition present formal model of the analyzed process using a set of system analysis methods.Material and methods. System analysis methods, especially IDEF0 diagrams and activity diagrams, for estimation of medical expert’s agreement Cohen’s kappa was used.The results. Based on the specification documents and expert’s experience the spread description on the process the control of volume, duration, quality and conditions of medical service assignment by medical organizations conducted by medical insurance organization was presented. Inputs, outputs, elements of management and executives were determined. As a result of decomposition, subprocesess were presented within activity diagrams.Conclusions. The obtained results of research allows to conclude that there is a set of problems which appear when medical organizations send reports for getting financial resources for clinical service realization in the scope of compulsory health insurance program. On the grounds of determined problems, we can conclude that it is necessary to develop an intellectual information system for estimating clinical records concerning getting financial resources for clinical service. In respect that human factor influence on the main stages of the analyzed process, we propose to use fuzzy logic as an inference engine. The self-learning function of the system will provide case-based reasoning.